MEET Project: Toward the spreading of EGS across Europe - Dalmais, Eleonore; Genter, Albert; Trullenque, Ghislain; Leoutre, Eric; Leiss, Bernd; Wagner, Bianca; Mintsa, André Charles; Bär, Kristian; Rajšl, Ivan (Zenodo, 2019)
The MEET Project aims at boosting the development of EGS across Europe in various geological contexts (sedimentary, volcanic, metamorphic and crystalline) by different approaches. This project, funded under EU Horizon 2020 grant program, has started in May 2018 and will last until October 2021. In regard to temperature, the MEET consortium will jointly demonstrate the opportunity to use proven low temperature resources (<90°C) from existing deep wells by finding the best material to avoid scaling and corrosion issues, by minimizing thermo-mechanical impacts in the cooled reservoirs (e.g. induced seismicity) as well as by testing innovative mobile ORC (Organic Rankine Cycle) to boost the electricity production. These low temperature resources will be provided by using oil wells or by lowering the reinjection temperature of operating EGS plants. The use of such existing wells will diminish the upfront investment, thus de-risking EGS and lowering their LCOE. In regard to mass flow, geological investigation of Variscan metasediment together with outcropping crystalline rocks will help the development of the enhancing strategies in such geological settings which are widely spread across Europe. Enhancement of permeability through the application of soft chemical stimulation concept will be carried out on new geothermal boreholes drilled in late Variscan granites in Cornwall. To support this program, various demo-sites have been selected to perform studies and experiments. These demo-sites represent various geological settings widely present in Europe: granites in Cornwall (UK) and Soultz-sous-Forêts (France), metamorphic sedimentary rocks in Havelange (Belgium) and Göttingen (Germany), oil field in Paris and Aquitanian sedimentary basins (France) and volcanic rocks in Reykjanes (Iceland). Finally, a map at European scale of all the compiled geological and technical information along with the development of a decision making tool will provide a useful mean to assess where future capacities should be installed.